Comparing Meta‐analysis and Individual Person Data Analysis Using Raw Data on Children's Understanding of Equivalence. Issue 6 (25th March 2018) - Hornburg, Caroline Byrd; Wang, Lijuan; McNeil, Nicole M.
Abstract : A prevailing theory of mathematical problem solving predicts that children will be less accurate solving a  +  b  =  c  + __ problems versus a  +  b  = __ +  c . However, this has never been tested directly. Because of low base rates, information combined from multiple studies can help improve estimation accuracy and precision. This study compared meta‐analysis and individual person data (IPD) analysis using raw data from 14 studies ( N  =   1, 414; n s = 30–232; M age reported = 8;7). Substantive results challenge the prevailing theory. Methodological results demonstrate the advantages of using meta‐analysis and IPD over single‐study analysis. Moreover, IPD can be more powerful than meta‐regression for detecting between‐study moderation effects. Abstract : The title for this Special Section isMeta‐analysis and Individual Participant Data Synthesis in Child Development, edited by Glenn I. Roisman and Marinus H. van IJzendoorn